Sinomenine Suppresses Development of Hepatocellular Carcinoma Cells via Inhibiting MARCH1 and AMPK/STAT3 Signaling Pathway - Yang, Wei; Feng, Qihua; Li, Minjing; Su, Jiaqi; Wang, Peiyuan; Wang, Xu; Yin, Yancun; Wang, Xia; Zhao, Mingdong (Frontiers in Molecular Biosciences, 2021)
Promotion of apoptosis and suppression of proliferation in tumor cells are popular strategies for developing anticancer drugs. Sinomenine (SIN), a plant-derived alkaloid, displays antitumor activity. However, the mechanism of action of SIN against hepatocellular carcinoma (HCC) is unclear. Herein, several molecular technologies, such as Western Blotting, qRT-PCR, flow cytometry, and gene knockdown were applied to explore the role and mechanism of action of SIN in the treatment of HCC. It was found that SIN arrests HCC cell cycle at G0/G1 phase, induces apoptosis, and suppresses proliferation of HCC cells via downregulating the expression of membrane-associated RING-CH finger protein 1 (MARCH1). Moreover, SIN induces cell death and growth inhibition through AMPK/STAT3 signaling pathway. MARCH1 expression was silenced by siRNA to explore its involvement in the regulation of AMPK/STAT3 signaling pathway. Silencing MARCH1 caused downregulation of phosphorylation of AMPK, STAT3 and decreased cell viability and function. Our results suggested that SIN inhibits proliferation and promotes apoptosis of HCC cells by MARCH1-mediated AMPK/STAT3 signaling pathway. This study provides new support for SIN as a clinical anticancer drug and illustrates that targeting MARCH1 could be a novel treatment strategy in developing anticancer therapeutics.